GENDER AND CRIME: ANALYSIS OF THE VULNERABILITY OF LGBTQ+ PEOPLE IN THE CONTEXT OF CRIME AND THE CRIMINAL JUSTICE SYSTEM (International Seven Journal of Multidisciplinary, 2025)
Analyzing the vulnerability of LGBTQ+ people in the context of crime and the criminal justice system reveals a complex intersection between gender, sexual orientation, and structural inequality. Historically marginalized and criminalized, these identities face systematic discrimination at every stage of the legal process, from police intervention to arrest and trial. The justice system, often reflecting and reinforcing heteronormative gender norms, perpetuates abuses and inequalities. This article explores how these practices affect LGBTQ+ people, discussing the flaws in public policy and proposing recommendations for a more inclusive and equitable approach.